Armenian: modern Eastern Armenian - Dum-Tragut, Jasmine (London Oriental and African language library 1382-3485, 2009)
This grammar of Modern Eastern Armenian gives a precise and explicit description of the Eastern Armenian language of the Republic of Armenia. It covers not only the normative tradition but, more importantly, also describes the colloquial language as it is used in Armenia today. With regard to methodological approach and terminology it fully meets the demands of modern general linguistics and typology. This grammar will be of interest not only to the specialised readership of descriptive and comparative linguists, of typologists and of armenologists, but to all those who would like to acquaint